The Effect Of Influencer Credibility, Persuasive Communication Ability, Disclosure Of Sponsorsip And Brand Awareness On The Purchase Decision Of Skintific Skincare Products On The Shopee Platform In Bengkulu City - Ambarwati, Ambarwati; Hidayati, Arifah; Safrianti, Sintia (JMB : Jurnal Manajemen dan Bisnis, 2025)
The purpose of this study is to determine how much influence Influencer Credibility, Persuasive Communication Skills, Disclosure of Sponsorship and Brand Awareness have on Purchasing Decisions for Skintific Skincare Products Shopee Platform in Bengkulu City. The method in this study is quantitative research. The sampling technique is purposive sampling. the data comes from the distribution of questionnaires (Google Form) which will be distributed online to consumers who have purchased Skintific Skincare Products Shopee Platform in Bengkulu City. The population of this study is consumers who have purchased Skintific Skincare Products Shopee Platform in Bengkulu City, researchers used the hair formula where 24 indicators x 5 = 120 respondents. This study uses a Likert scale, with SPSS 25 tools. The results of this study are; (1) Influencer credibility has a significant effect on purchasing decisions for Skintific Skincare Products on the Shopee Platform in Bengkulu City, (2) Persuasive Communication Skills have a significant effect on purchasing decisions for Skintific Skincare Products on the Shopee Platform in Bengkulu City, (3) Disclosure of Sponsorship has a significant effect on purchasing decisions for Skintific Skincare Products on the Shopee Platform in Bengkulu City (4) Brand Awareness has a significant effect on purchasing decisions for Skintific Skincare Products on the Shopee Platform in Bengkulu City and (5) There is a simultaneous influence of the variables Influencer Credibility, Persuasive Communication Skills, Disclosure of Sponsorship and Brand Awareness on Purchasing Decisions for Skintific Skincare Products on the Shopee Platform in Bengkulu City.